PREDIKTOR KINERJA INTERNAL AUDITOR PADA PT ASTRA MOTOR PROVINSI BALI - Dewi, Ni Ketut Junika; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This research aims to analyze the implementation of good governance, locus of control, audit structure and leadership style as a predictor of the performance of the internal auditor at PT Astra Honda Motor Bali Province. Study choose throughout the sales office of PT Astra Honda Motor Bali Province to make the auditors were 84 people in the sample with saturated sample method. Data distribution of the questionnaire by adopting the technique of multiple linear regression analysis. Yield data provide answers to the application of good governance, locus of control, audit structure and leadership style contributed as much as 85.5 percent on the performance of the internal auditor, while the remaining 14.5 percent is influenced by other variables not included in the research model.
Keywords: good governance, locus of control, audit structure, leadership style, and performance of auditors